Criminological Research On Modern Vandalism In Ukraine - Salaieva, Karyna; Lukashevych, Serhii (Archives of Criminology and Forensic Sciences, 2022)
Summary. The article is devoted to the study of modern vandalism in Ukraine from the point of view of criminology. Both official statistical information and the results of the authors’ own research were analysed. It has been proven that modern vandalism in Ukraine should be criminalized and its characteristics included in the Criminal Code as aggravating circumstances. The researchers came to a general conclusion about the need for further study of the problem described. The objective of the article is to study crimes related to vandalism as an object of criminological analysis. At the same time, a number of scientific tasks were solved: the question of the essence of vandalism as a manifestation of illegal aggressive behavior was clarified; the determinants of modern vandalism are separate; the genesis of vandalism-related crimes has been investigated, their causes and conditions have been determined, etc. Research methods. The methodological basis of the work is the dialectical method, the application of which allows you to study the object and subject of research in their epistemological unity, their interrelation, as well as the differences in vandalism as a manifestation of aggressive behavior illegal. Using the historical method, historical and general theoretical questions of the essence of vandalism have been clarified. Using the methods of analysis and synthesis, the types of modern vandalism are separated. This was also facilitated by the use of the structural and functional method which was applied at the same level as the classification and grouping methods in the criminological analysis of crimes related to vandalism and the determination of their latency. The methods specified also made it possible to investigate the genesis of crimes related to vandalism, to determine their causes and conditions and to submit the personality of the criminal-vandal to a criminological analysis. The logical and semantic method was used to provide its own definition of vandalism. Concrete sociological and statistical methods of collecting and analyzing empirical material were also applied, questionnaires of scientific, scientific-pedagogical and practical workers regarding the latency of crimes related to vandalism and the study of documents.